Penentuan Evaluasi Kinerja Karyawan Berbasis Logika Fuzzy Mamdani - Muharni, Muharni; Awaliah, Widiarti; Surianto, Dewi Fatmarani (PT. Lontara Digitech Indonesia, 2024)
Fuzzy logic refers to a form of logic derived from fuzzy set theory, which is used for estimation reasoning. In this context, fuzzy logic allows us to represent and process linguistic information and subjective attributes related to the real world. This study aims to apply the Fuzzy Mamdani method in determining employee performance evaluations at PT. Luwu Tongkonan Utama, Tonasa cement distribution company. This method is used to overcome uncertainty in evaluating employee performance by converting numerical data into linguistic data. The results of this study can show that fuzzy mamdani can be used to measure employee performance. Of the 31 data used, 29 employees are included in the good set, while the other 2 employees have very good performance.